Primary intracardiac malignant peripheral nerve sheath tumor: A rare case report - Sudheer Arava; Saphalta Bagmar; Parul Jain; Muthu Kumaran; Sanjeev Kumar; Ruma Ray (Wolters Kluwer Medknow Publications, 2015)
Myxomas are the most common benign cardiac tumors constituting approximately 75% of all the cardiac tumors. Rest 25% are malignant and sarcomas being the commonest. Among the sarcomas primary cardiac malignant peripheral nerve sheath tumors are extremely rare. They usually arise in relation to the branches of vagus or phrenic nerves, 5-42% being associated with neurofibromatosis type 1. Clinical signs and symptoms depend on the location and extent of involvement. Complete resection is the treatment of choice but local recurrence is common.